2020
DOI: 10.1371/journal.pone.0227199
|View full text |Cite|
|
Sign up to set email alerts
|

Transgenic overexpression of endogenous FLOWERING LOCUS T-like gene MeFT1 produces early flowering in cassava

Abstract: Endogenous FLOWERING LOCUS T homolog MeFT1 was transgenically overexpressed under control of a strong constitutive promoter in cassava cultivar 60444 to determine its role in regulation of flowering and as a potential tool to accelerate cassava breeding. Early profuse flowering was recorded in-vitro in all ten transgenic plant lines recovered, causing eight lines to die within 21 days of culture. The two surviving transgenic plant lines flowered early and profusely commencing as soon as 14 days after establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted February 12, 2021. ; https://doi.org/10.1101/2021.02.11.430817 doi: bioRxiv preprint expressed at higher levels in '0002 (early genotype) than in '419 (late genotype) while the over expression studies of MeFT1 by [15] further confirmed its florigenic properties. The role of FT as a mobile long distance signaling peptide that moves from leaf to shoot apical meristem to induce flowering has long been established in Arabidopsis [14,45].…”
Section: Vegetative Growth Showed Complexity Between Field and Contromentioning
confidence: 84%
See 3 more Smart Citations
“…CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted February 12, 2021. ; https://doi.org/10.1101/2021.02.11.430817 doi: bioRxiv preprint expressed at higher levels in '0002 (early genotype) than in '419 (late genotype) while the over expression studies of MeFT1 by [15] further confirmed its florigenic properties. The role of FT as a mobile long distance signaling peptide that moves from leaf to shoot apical meristem to induce flowering has long been established in Arabidopsis [14,45].…”
Section: Vegetative Growth Showed Complexity Between Field and Contromentioning
confidence: 84%
“…The overexpression of Arabidopsis FT in cassava [4, 16] and of a native FT gene in cassava [15] resulted in significantly earlier flowering in late cassava genotypes. These early flowering phenotypes were accompanied by significantly reduced number of nodes to forking [4, 15], thus confirming that earliness is associated with a reduction number of nodes to fork type branching. Furthermore, [5] showed that the late-flowering genotype ‘419 initiates flowers at 22°C but not at warmer temperatures, which is in agreement with the current findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations into the reproductive biology of cassava has led to the development of several potential interventions to improve reproductive performance in cassava: transgenic intervention by overexpressing Flowering Locus FT (Adeyemo et al 2017;Odipio et al 2020;Bull et al 2017), modulating photoperiod and temperature to accelerate flowering time (Adeyemo et al 2019), application of silver thiosulfate to enhance flower development and longevity (STS) (Hyde et al 2020), or pruning young subtending branches to alleviate flower abortion (Pineda et al 2020). None so far has focused on increasing the proportion of female flowers.…”
Section: Introductionmentioning
confidence: 99%